Potential Pathways Associated With Exaggerated T Follicular Helper Response in Human Autoimmune Diseases - Horiuchi, Shu; Ueno, Hideki (Frontiers in Immunology, 2018)
Convincing lines of evidence in both mice and humans show that exaggerated Tfh response is pathogenic in autoimmune diseases. A recent positive outcome of ustekinumab in a Phase II trial in active systemic lupus erythematosus provides new evidence that T cells can be a therapeutic target for autoantibody-mediated autoimmune diseases. However, the cause of exaggerated Tfh response in humans is still much less clear than in mouse models where genetic factors can be manipulated for in vivo testing. Nonetheless, recent advance in our understanding on the mechanisms of human Tfh differentiation, and identification of multiple risk loci in genome-wide association studies have revealed several pathways potentially associated with exaggerated Tfh response in human autoimmune diseases. In this review, we will first briefly summarize the differentiation mechanisms of Tfh cells in humans. We describe the features of “Tfh-like” cells recently identified in inflamed tissues of human autoimmune diseases. Then we will discuss how risk loci identified in GWAS are potentially involved in exaggerated Tfh response in human autoimmune diseases.